Biological trait composition of macrofauna from mudflats along south-east Queensland, Australia - Dissanayake, Navodha G; Frid, Christopher L J; Caswell, Bryony A (In: Dissanayake, NG et al. (2020): Biodiversity, trait composition and ecological functioning: impacts of coastal urbanisation on subtropical mudflats [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.915865, 2020)
Species biological traits were analysed using biological traits analysis which captured their life habit, morphology and behaviour (see accompanying paper for methods; doi:/10.1071/MF19242). The biological traits of mudflat macrofauna assemblages were compared to determine the effects of urbanisation on ecological functioning and delivery of ecosystem services of mudflats. The data revealed that functioning was conserved in mudflats experiencing current levels of enrichment, but this may decline with growing pressure from human populations. A total of 50 macrofaunal taxa were observed across 24 mudflats in both winter 2016 and summer 2017. Eleven biological traits (e.g. morphological, life history and behavioural traits) and a total of 45 trait modalities were selected. Each trait was divided into 3-5 categories known as trait modalities. The selected modalities contribute either directly or indirectly to vital ecosystem functions such as organic matter decomposition, sediment oxygenation, primary productivity and food for predators. For each trait, the affinity of each taxon to every modality was assigned and the total affinity for each trait summed to '1'. Splitting the value of one between the trait modalities of a single trait is called 'fuzzy coding'. The trait modality with highest affinity was assigned a value of '1' and for the modalities with the lowest affinity was given a value of '0'.
Keywords: Biological traits; ecosystem dynamics; intertidal; Macrofauna; south east Queensland